Two-year outcome after recurrent first trimester miscarriages: prognostic value of the past obstetric history - Kling, Christiane; Magez, Julia (Archives of gynecology and obstetrics, 2016)
PurposeRecurrent miscarriage (RM) is a stressful condition which gives rise to extensive diagnostic evaluation and is seen as a potentially curable maternal disease. Nevertheless, epidemiological data have shown that outcome is related to fertility. In addition to maternal age and number of preceding miscarriages, further markers derived from the past history may support counselling.MethodsObservational trial comprising 228 couples who were referred between 1996 and 2003 for immunological evaluation at maternal ages 20-39 years after three or more spontaneously conceived primary first trimester miscarriages. They were interviewed in 2005, ongoing pregnancies were followed up until birth in 2006. Past obstetric history was correlated with 2 year cumulative pregnancy and delivery rates (CPR, CDR).ResultsCPR and CDR were 206/228 (90.4 %) and 174/228 (76.4 %). Duration of infertility was associated with lower CPR (up to 3/>3 years, p < 0.01), whereas age and number of preceding losses inversely correlated with CDR (<35 years/35-39 years, p < 0.002; 3/>3 miscarriages, p < 0.002). Detection of an embryonic heart beat in 2-3 of the first three miscarriages resulted in favourable outcome (CPR: p < 0.02, CDR: p < 0.002). Prognosis was excellent in younger fertile women after three miscarriages where vital signs had been detected; under less favourable conditions not only risks for further miscarriage, but also for secondary infertility were elevated.ConclusionSecondary infertility is a feature of RM. Embryonic vital signs in preceding pregnancies are prognostic markers and should be regarded as a strong confounding factor in trials on therapeutic interventions. Prevention may be more appropriate than treatment.
Gesehen am 18.10.2019